Simplify: {36 ÷ (-9)} ÷ {(-24) ÷ 6)
2 answers:
Answer:
1
Step-by-step explanation:
{36 ÷ (-9)} ÷ {(-24) ÷ 6}
= (-4) ÷ (-4)
= 1
Answer:
1
Step-by-step explanation:
{36 ÷(-9)} ÷ {(-24) ÷ 6)
{36 ÷ -9} ÷ {-24 ÷ 6}
(-4) ÷ (-4)
1
using BODMAS rule (Bracket 0f Division , Multiplication and Addition , Subtraction)
Rule
first small bracket ( ) must be solved
then curly bracket { }
then only big bracket [ ]
remebere while dividing -4 and -4 along with the numbers - signs also gets cancel. So ur answer is positive.
You might be interested in
It all started by increasing the number of the years each year people buy Starbucks and every year it increasing <span />
Y = -3x + 6 = 9
-3x = 3
x = -1
solution is (-1, 9)
Answer:
C. 6 ft
Step-by-step explanation:
If Marvin's son is 3 feet tall with a 1 foot shadow, Marvin would be 6 feet tall with a 2 foot shadow.
Answer: first answer choice
Step-by-step explanation:
15.Dylan has 400 more
17. 426 divided by 10= 42.6